Ischemia–reperfusion injury after spinal cord decompressive surgery—An in vivo rat model - Boyu Zhang; Zhefeng Jin; Pengren Luo; He Yin; Xin Chen; Bowen Yang; Xiaokuan Qin; LiGuo Zhu; Bo Xu; Guoliang Ma; Dian Zhang (Animal Models and Experimental Medicine)
Abstract Background Although decompression surgery is the optimal treatment for patients with severe degenerative cervical myelopathy (DCM), some individuals experience no improvement or even a decline in neurological function after surgery, with spinal cord ischemia–reperfusion injury (SCII) identified as the primary cause. Spinal cord compression results in local ischemia and blood perfusion following decompression is fundamental to SCII. However, owing to inadequate perioperative blood flow monitoring, direct evidence regarding the occurrence of SCII after decompression is lacking. The objective of this study was to establish a suitable animal model for investigating the underlying mechanism of spinal cord ischemia–reperfusion injury following decompression surgery for degenerative cervical myelopathy (DCM) and to elucidate alterations in neurological function and local blood flow within the spinal cord before and after decompression. Methods Twenty‐four Sprague–Dawley rats were allocated to three groups: the DCM group (cervical compression group, with implanted compression material in the spinal canal, n = 8), the DCM‐D group (cervical decompression group, with removal of compression material from the spinal canal 4 weeks after implantation, n = 8), and the SHAM group (sham operation, n = 8). Von Frey test, forepaw grip strength, and gait were assessed within 4 weeks post‐implantation. Spinal cord compression was evaluated using magnetic resonance imaging. Local blood flow in the spinal cord was monitored during the perioperative decompression. The rats were sacrificed 1 week after decompression to observe morphological changes in the compressed or decompressed segments of the spinal cord. Additionally, NeuN expression and the oxidative damage marker 8‐oxoG DNA were analyzed. Results Following spinal cord compression, abnormal mechanical pain worsened, and a decrease in forepaw grip strength was observed within 1–4 weeks. Upon decompression, the abnormal mechanical pain subsided, and forepaw grip strength was restored; however, neither reached the level of the sham operation group. Decompression leads to an increase in the local blood flow, indicating improved perfusion of the spinal cord. The number of NeuN‐positive cells in the spinal cord of rats in the DCM‐D group exceeded that in the DCM group but remained lower than that in the SHAM group. Notably, a higher level of 8‐oxoG DNA expression was observed, suggesting oxidative stress following spinal cord decompression. Conclusion This model is deemed suitable for analyzing the underlying mechanism of SCII following decompressive cervical laminectomy, as we posit that the obtained results are comparable to the clinical progression of degenerative cervical myelopathy (DCM) post‐decompression and exhibit analogous neurological alterations. Notably, this model revealed ischemic reperfusion in the spinal cord after decompression, concomitant with oxidative damage, which plausibly underlies the neurological deterioration observed after decompression.